Barley germoplasm characterization using agronomic and quality traits - Castro, A.; Ernst, O.; Hoffman, E.; Bentancur, O. (Agrociencia Uruguay, 2022)
Forty-six malting barley genotypes, including five commercial varieties, were evaluated in two years in order to characterize the genetic variability in breeding use in Uruguay, and its potential to over yield the varieties currently in use. The two analyzed years presented highly contrasting climatic characteristics. The genotypes were grouped according to their relative performance in the two years for a group of fourteen agronomic and grain quality traits. A cluster analysis was carried out, and the traits responsible for each cluster separation, were studied. The checks showed the ability to maintain a good grain yield and quality level in stressing climatic conditions. In the high yield year, several introduced genotypes exceeded the best checks, but they failed to maintain that superior performance in stressing climatic conditions. This performance was associated to longer cycles to anthesis and shorter grain-filling periods, which hinder the adaptation to national conditions. The use of introduced germplasm resulted in an inefficient way of reaching high yield potentials with high and stable grain quality.